Исследование системы коррекции звука с учётом характеристик помещения - Ашихмин, В. О. (ХНУРЕ, 2019)
In this paper, a technique has been developed for measuring the end-to-end frequency response and phase response of the sound system under study. Used RAV software for research. The best type of test signals was selected to tune the end-to-end equalization system and the necessary correction filter resolution. The possibilities of the system of through equalization are experimentally investigated, the limitations of its use are determined. The equalization system allowed to reduce the non-uniformity of the frequency response from 12 to 4 dB